Production sharing contracts of oil and gas in Kurdistan region of Iraq - Sharif, Sabah Karim (Kulliyyah of Laws,International Islamic University Malaysia, 2014)
Nearly all oil and Gas in the world is developed through some form of contracts and for more than a century the petroleum contracts, as a basic legal tool, have played a crucial role between the contractual parties in the petroleum sector. The development of these sorts of contracts demonstrates the dynamic changes that have occurred in the petroleum industry. Relevant to the question of balancing the interests between the host state (HS) and the international oil company (IOC), this study examines the contractual measures that have been followed by the parties to create fair and adequate relationship, and also keep the contractual interests in a mutual and balanced manner. Furthermore, this study discusses the structure of the petroleum contracts with a special reference to the main terms of the KRG's Production Sharing Contracts. As a subsidiary concentration, the researcher also draws attention to the Kurdistan Region oil and gas law, the Iraqi constitutional approach of the region and the governorate's authority in striking oil and gas development contracts. This research applies a descriptive method to attain its objectives in its main discussions about the main features of the production sharing contracts in the Kurdistan Region of Iraq, the balance of interests between the host state and investor (IOC) under KRG's PSCs and the contractual mechanisms to guarantee the balance of interests between the host state and the investors in the KRG's PSC. Also this study shall seek the examination of the contractual relational outcome under the petroleum production contracts and their mechanisms. It will also take an analytical and critical assessment to evaluate the difficulties encountered in achieving fair interests for both parties. The current study's findings show that, the PSC is a suitable instrument for the Kurdistan Region of Iraq to build up its domestic industry with the assistance of foreign oil companies. This research has also proven that these mechanisms are the main devices to encourage the parties to protect their interests and keep the balance of their relations during the life time of the contract. By adopting a range of mechanisms which are fair and flexible to both parties (HS & IOC) and adapted to any unpredictable changes that may take place with time, the KRG creates a reasonable environment for the International Oil Companies (IOC) to invest in its petroleum sector and keeps the parties' interest in a balanced manner. Hence, this study has shown that by introducing a flexible PSC and reasonable mechanisms, the Kurdistan Region of Iraq has its own strategy for developing its petroleum sector and has established itself as an attractive region for foreign investment.